Managing the Message: The Effects of Firm Actions and Industry Spillovers on Media Coverage Following Wrongdoing - Zavyalova, Anastasiya; Pfarrer, Michael D.; Reger, Rhonda K.; Shapiro, Debra L. (Academy of Management Journal, 2012)
We contribute to research on the management of social perceptions by considering the relative effectiveness of a firm's technical and ceremonial actions in managing media coverage after its own or its competitors' wrongdoing. We examine these relationships in the context of product recalls by U.S. toy companies over the ten-year period 1998–2007. As hypothesized, firms with higher levels of wrongdoing experience less positive media coverage; however, this decline is mitigated during periods of higher industry wrongdoing. Additionally, we find support for a negative spillover effect: the tenor of media coverage about a focal firm is less positive if others in its industry recall products. Further, technical actions help firms attenuate the negative effect of their own wrongdoing on the tenor of media coverage, whereas ceremonial actions amplify this effect. In contrast, ceremonial actions are more effective in attenuating the negative effect of industry wrongdoing on the tenor of media coverage about a focal firm.